Coronary Artery Bypass Grafting 2022
DOI: 10.5772/intechopen.103782
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Problems in Coronary Artery Diseases

Abstract: Coronary artery disease (CAD) remains the leading cause of mortality among cardiovascular diseases, responsible for 16% of the world’s total deaths. According to a statistical report published in 2020, the global prevalence of CAD was estimated at 1655 per 100,000 people and is predicted to exceed 1845 by 2030. Annually, in the United States, CAD accounts for approximately 610,000 deaths and costs more than 200 billion dollars for healthcare services. Most patients with CAD need to be treated over long periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
169
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(196 citation statements)
references
References 58 publications
4
169
1
Order By: Relevance
“…seemed to play an important role in accelerating response/recovery process of gas sensors of graphene-based heterostructure composite sensing materials as well as improving gas response. [95,[106][107][108][109][110] Cui et al reported that the rGO modified with Ag nanoparticles showed higher response to NH 3 with faster response/recovery speed(response/ recovery time:6 s/10 s) than that of pristine rGO based sensor (Figure 5a). [95] The response/recovery time was defined as the time needed for a sensor to change/recover more than 63.2% of the maximum sensitivity.…”
Section: Graphene-noble Metal Compositementioning
confidence: 99%
See 1 more Smart Citation
“…seemed to play an important role in accelerating response/recovery process of gas sensors of graphene-based heterostructure composite sensing materials as well as improving gas response. [95,[106][107][108][109][110] Cui et al reported that the rGO modified with Ag nanoparticles showed higher response to NH 3 with faster response/recovery speed(response/ recovery time:6 s/10 s) than that of pristine rGO based sensor (Figure 5a). [95] The response/recovery time was defined as the time needed for a sensor to change/recover more than 63.2% of the maximum sensitivity.…”
Section: Graphene-noble Metal Compositementioning
confidence: 99%
“…[26] It was known that [95] Copyright 2013, The Authors, Published by Royal Society of Chemistry. rGO/Ag [106] Nanowires NH 3 RT 0.1% in Ar (R g −R 0 )/R 0 = 28% 200/60 rGO/Ag [95] Flake NH 3 RT 2500 (R g −R 0 )/R 0 = 7.7% 6/10 (>63.2% response) rGO/Ag [107] rGO as over-coating layer on Ag NPs and Ag NWs NH…”
Section: Graphene-metal Oxide Compositementioning
confidence: 99%
“…Similar chemical shift of the C2 peak in ZIF-8 has been observed when organic molecules, such as caffeine, were encapsulated in the pores of ZIF-8 to form van der Waals bonds. 28 However, more detailed analysis supported by DFT calculations 29 would be required to further proof electrostatic interactions and hydrogen bonding between the ZIF-8 and C–N groups of the PAN nanofiber (as visualized by the chemical formulas in Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48] Similarly, investigations by Tran et.al., has established Au nanoparticles as a catalyst for HER. [49] It is observed that the catalytic activity depends on the surface area projected by the nanoparticles which provides the best alternatives for Pt-free catalysis. Besides, Au catalysts also show good activity for water-gas shift reaction at low temperatures as compared to Pt catalysts.…”
Section: Introductionmentioning
confidence: 99%